2017
DOI: 10.1002/2016gb005567
|View full text |Cite
|
Sign up to set email alerts
|

N2O production and consumption from stable isotopic and concentration data in the Peruvian coastal upwelling system

Abstract: The ocean is an important source of nitrous oxide (N 2 O) to the atmosphere, yet the factors controlling N 2 O production and consumption in oceanic environments are still not understood nor constrained. We measured N 2 O concentrations and isotopomer ratios, as well as O 2 , nutrient and biogenic N 2 concentrations, and the isotopic compositions of nitrate and nitrite at several coastal stations during two cruises off the Peru coast (~5-16°S, 75-81°W) in December 2012 and January 2013. N 2 O concentrations va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
163
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(185 citation statements)
references
References 101 publications
(200 reference statements)
22
163
0
Order By: Relevance
“…Cross plots of SP versus δ 18 O‐N 2 O and δ 15 N α ‐N 2 O versus δ 18 O‐N 2 O showed similar positive slope, whereas 15 N β and 18 O had a slightly negative slope in this study (Figure ). A similar trend was also observed by Bourbonnais et al () at the Peruvian coastal upwelling system and seen as the clear mechanistic evidence for removal of N 2 O by denitrification. Hence, our study may suggest that N 2 O reduction occurred in the shelf and slope sediment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Cross plots of SP versus δ 18 O‐N 2 O and δ 15 N α ‐N 2 O versus δ 18 O‐N 2 O showed similar positive slope, whereas 15 N β and 18 O had a slightly negative slope in this study (Figure ). A similar trend was also observed by Bourbonnais et al () at the Peruvian coastal upwelling system and seen as the clear mechanistic evidence for removal of N 2 O by denitrification. Hence, our study may suggest that N 2 O reduction occurred in the shelf and slope sediment.…”
Section: Discussionsupporting
confidence: 88%
“…δ 15 N bulk ‐N 2 O, δ 15 N α , SP at the intermediate water and deep water correlated positively with δ 18 O‐N 2 O, while δ 15 N β correlated negatively with δ 18 O‐N 2 O (Figure c). This is thought to be a clear mechanistic evidence for removal of N 2 O by denitrification (Bourbonnais et al, ) or a sign of shift in the N 2 O production and consumption processes (Yamagishi et al, ). Furthermore, unlike the shallow and intermediate waters, no correlations between ∆N 2 O, AOU, and nitrate were observed for the deep waters in this study (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the anoxic and the peripheral suboxic waters (generally <10 μM O 2 ), our 15 N tracer incubation experiments showed that denitrification is the dominant source of N 2 O production, because rates of N 2 O production from NO 2 − and NO 3 − reduction were tenfold to 100‐fold higher than N 2 O production from NH 4 + oxidation. Similarly, using N 2 O natural abundance isotopes, a recent study concluded that incomplete denitrification caused N 2 O supersaturation in the Peruvian OMZ (Bourbonnais et al, ). Highest rates of N 2 O production from NO 2 − and NO 3 − reduction occurred just below the oxic‐anoxic interface, where O 2 inhibition of denitrification is relieved and availability of organic matter promotes denitrification.…”
Section: Discussionmentioning
confidence: 96%
“…N 2 O isotopomer analyses were performed post‐cruise at the University of Massachusetts Dartmouth using a GV IsoPrime continuous flow isotope ratio mass spectrometer, interfaced with a multicollector and customized purge‐and‐trap system (Bourbonnais et al, ). N 2 O measurements were standardized and corrected for the scrambling effect (Westley et al, ) using a set of reference N 2 O gases (EMPA CB08976, EMPA CB09715, EMPA CB09766 and EMPA 53504; Mohn et al, ) of known bulk and site‐specific isotopic composition.…”
Section: Methodsmentioning
confidence: 99%